2013
DOI: 10.1177/039463201302600412
|View full text |Cite
|
Sign up to set email alerts
|

Salso-Sulphide Thermal Water in the Prevention of Recurrent Respiratory Infections in Children

Abstract: Recurrent respiratory infections (RRI) represent a social problem for both the pharmaco-economic impact and the burden on the family. Thermal water is popularly well accepted. However, there is no scientific evidence of its preventive activity on recurrent respiratory tract infections (RRI). Therefore, the purpose of this study was to evaluate the effects of Agnano thermal water nasal irrigation on RRI prevention in children. A total of 107 children (70 males, mean age 4.5±1.2 years) with RRI were enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…On the other hand, it has to be considered that also saline solution could exert a preventive effect on RRI, as nasal lavage may be able of removing microbes, inflammatory cells and mediators. In this regard, it has been very recently demonstrated that thermal water was able of reducing the recurrence of R.I. in children with RRI [ 15 ]. Moreover, a recent double-blind, placebo-controlled, randomised, multicentre study investigated a group of children with RRI [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has to be considered that also saline solution could exert a preventive effect on RRI, as nasal lavage may be able of removing microbes, inflammatory cells and mediators. In this regard, it has been very recently demonstrated that thermal water was able of reducing the recurrence of R.I. in children with RRI [ 15 ]. Moreover, a recent double-blind, placebo-controlled, randomised, multicentre study investigated a group of children with RRI [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nasal irrigation with hypertonic saline significantly reduced the adenoid size in children with adenoid hypertrophy [114]. Salso-sulfide thermal water was successfully used in children with RRI [115]. Consistently, salsobromo-iodine thermal water reduced postnasal driprelated cough in children suffering from acute upper airway infection [116].…”
Section: Therapeutic Strategies For Ua Diseases Based On Local and Rementioning
confidence: 99%
“…Sulphurous mineral water inhalations and irrigations have been traditionally used to treat airway diseases [60–63]. According to Keller et al [64], compared to isotonic saline solution, sulphurous mineral water shows benefits and should be investigated further.…”
Section: Topical Transformations and Hazardsmentioning
confidence: 99%